2021
DOI: 10.3390/foods10040774
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intestinal Inflammation by Soybean and Soy-Derived Compounds

Abstract: Environmental factors, particularly diet, are considered central to the pathogenesis of the inflammatory bowel diseases (IBD), Crohn’s disease and ulcerative colitis. In particular, the Westernization of diet, characterized by high intake of animal protein, saturated fat, and refined carbohydrates, has been shown to contribute to the development and progression of IBD. During the last decade, soybean, as well as soy-derived bioactive compounds (e.g., isoflavones, phytosterols, Bowman-Birk inhibitors) have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 258 publications
1
27
0
Order By: Relevance
“…With extensive recent developments in immunology, the concept of innate immunity and its relationship with diseases have created major interest in the scientific community. Inflammatory reactions inevitably appear in response to all stimuli in daily life, but they differ in severity [131][132][133]. When our body is healthy or when the infection is weak, it can control the inflammatory response and recover to normal, but when the ability to control the inflammatory response is weakened, the damage caused by inflammation can be more severe, leading to disease [133].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…With extensive recent developments in immunology, the concept of innate immunity and its relationship with diseases have created major interest in the scientific community. Inflammatory reactions inevitably appear in response to all stimuli in daily life, but they differ in severity [131][132][133]. When our body is healthy or when the infection is weak, it can control the inflammatory response and recover to normal, but when the ability to control the inflammatory response is weakened, the damage caused by inflammation can be more severe, leading to disease [133].…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Soybeans contain a diverse array of health functional substances, the most representative of which are isoflavones. Soy isoflavones inhibit cancer cell growth by suppressing the expression of tyrosine kinase which has positive role in cancer cell growth, physiology, and division, while inducing apoptosis and controlling cell cycle [132]. In addition, soy isoflavones exhibit anticancer activity by inhibiting vasculogenesis which promotes cancer cell growth and metastasis as well as the migration to and activation in the nucleus of the transcription factor NF-κB (Figure 9) [147].…”
Section: Anticarcinogenic Activity Through Gene Regulationmentioning
confidence: 99%
“…Among the natural materials, soybeans have drawn substantial attention since they have been reported to contain various bioactive compounds, including tocopherols, soyasaponins, and isoflavones [ 18 , 19 ]. These functional substances not only improve metabolic and cardiovascular functions but also help to prevent obesity [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study revealed that the intake of dietary daidzein significantly increased the population of two equol-generating bacteria, Slackia isoflavoniconvertens and Asaccharobacter celatus [ 116 ]. Moreover, numerous studies conducted in humans and rodents showed that consumption of soy or soy food products affects intestinal ecology [ 114 , 117 , 118 , 119 , 120 ]. It was also stated that the total amount and/or relative percentage of the particular microbial ecosystem in the intestine might be altered by genistein in food or supplemental forms [ 121 ].…”
Section: Effect Of Different Phytochemical Compounds On the Modulatio...mentioning
confidence: 99%